2022
DOI: 10.4037/ccn2021152
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Partnership Between Intensive Care Unit Nurses and Therapists to Care for Patients With COVID-19

Abstract: Background When patients with COVID-19 began presenting to hospitals in early 2020, medical professionals were unprepared to handle the severity of disease and the number of severely ill patients. Local Problem In response to critical needs of patients with COVID-19 and the threat of nurse burnout, a special operations team comprising physical and occupational therapists was convened to (1) provide help to intensive care unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The data collection phase (July 2021) occurred during the Covid-19 pandemic, but this was not cited by participants as a factor in reducing or supporting use of outcome measures. However, their use may have decreased during the acute response phases to the pandemic, as practice priorities by NHS and social care staff shifted from gathering data to supporting hospital colleagues in intensive care work (Reese et al , 2021), or moving medically well in-patients back into their community settings at pace. Increased use of outcome measures may now be evident as the pandemic no longer constitutes a global health emergency (World Health Organisation, 2023), but this topic would need further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data collection phase (July 2021) occurred during the Covid-19 pandemic, but this was not cited by participants as a factor in reducing or supporting use of outcome measures. However, their use may have decreased during the acute response phases to the pandemic, as practice priorities by NHS and social care staff shifted from gathering data to supporting hospital colleagues in intensive care work (Reese et al , 2021), or moving medically well in-patients back into their community settings at pace. Increased use of outcome measures may now be evident as the pandemic no longer constitutes a global health emergency (World Health Organisation, 2023), but this topic would need further study.…”
Section: Discussionmentioning
confidence: 99%
“…Bowman (2006) found lack of knowledge was a barrier to outcome measure use in Australian hospital and community settings. Additionally, a multi-disciplinary frailty team in England (Coker et al, 2019) found barriers to use of the Clinical Frailty Scale (Rockwood et al, 2005), which included lack of knowledge, lack of consistency in scoring and a dislike of "pigeon holing" clients. Therapists need to balance time constraints to build knowledge and use outcome measures demonstrate the effectiveness of occupational therapy.…”
Section: Factors Affecting Usementioning
confidence: 99%
“…SARS-CoV-2, the virus responsible for the syndrome COVID-19, has caused many paradigm shifts in health care and rehabilitation 1–3. The strains on the health care system during a pandemic characterized by an increased incidence of severe respiratory failure have meant that paradigm shifts are especially profound in the intensive care unit (ICU) 4,5. Patients with COVID-19 often experience respiratory failure but may have additional symptoms including anorexia, nausea and diarrhea, myocarditis, skeletal muscle myopathy, and generalized debility 6–14.…”
mentioning
confidence: 99%
“…[1][2][3] The strains on the health care system during a pandemic characterized by an increased incidence of severe respiratory failure have meant that paradigm shifts are especially profound in the intensive care unit (ICU). 4,5 Patients with COVID-19 often experience respiratory failure but may have additional symptoms including anorexia, nausea and diarrhea, myocarditis, skeletal muscle myopathy, and generalized debility. [6][7][8][9][10][11][12][13][14] These patients are at risk of substantial deconditioning as they are confined to bed from systemic symptoms as well as profound hypoxemia.…”
mentioning
confidence: 99%